ACTIVITY TEST OF LEMONGRASS LEAF EXTRACT (CYMBOPOGON CITRATUS) AGAINST STREPTOCOCCUS MUTANS BACTERIA AND ESCHERCHIA COLI - Sakinah, Nurul (LPPM Universitas Bina Mandiri Gorontalo, 2023)
ABSTRACT This study aims to determine the antibacterial activity of lemongrass leaf extract (Cymbopogon citratus) against Streptococcus mutans and Escherchia coli bacteria. This research method uses a Complete Randomized Design (RAL) consisting of 7 treatments and 4 repeats. The treatments are: P1 (negative control), P2 (10% concentration), P3 (20% concentration), P4 (30% concentration), P5 (40% concentration), P6 (50% concentration) and P7 (Amoxicillin positive control). The results showed that the concentration of lemongrass leaf extract (Cymbopogon citratus) has activity to inhibit the growth of Streptococcus mutans and Escherchia coli bacteria. The results of the statistical analysis of the Kruskall Wallis test showed a significant value of 0.008 or <0.05, so it can be said that there is a dose of lemongrass leaves (Cymbopogon citratus) against the growth of Streptococcus mutans bacteria. The processed data using the Kruskall Wallis test on Escherchia coli bacteria showed a significant value of 0.002 or <0.05, so it can be said that there is a dose of lemongrass leaves (Cymbopogon citratus) against Escherchia coli bacteria. Further tests (Duncan Test) found that there was no significant difference between one concentration and another, so it can be said that the optimum concentration of lemongrass leaf extract treatment (Cymbopogon citratus) in inhibiting the growth of Streptococcus mutans and Escherchia coli bacteria is at a concentration of 50%